Psychological Risk Management: Mitigating the Impact of Future Uncertainty on Student Learning Motivation - Lazwardhi Izhar; Wahyu Hidayat (Institut Agama Islam Persis Bandung, 2025)
Entering the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era, both global and local educational landscapes are confronted with an escalation of future uncertainty that fundamentally burdens the psychological well-being of students. This study aims to investigate the causality between future uncertainty and student learning motivation, as well as to examine the efficacy of social support as a psychological buffer within the Indonesian sociocultural context. Employing a cross-sectional correlational design with a quantitative approach, data were collected through a multistage stratified random sampling technique and analyzed using Structural Equation Modeling (SEM). The empirical investigation reveals that future uncertainty predominantly degrades both intrinsic and extrinsic learning motivation by dismantling students' success expectations and task value. Nevertheless, the analysis confirms that a robust social support ecosystem comprising family, educators, and peers significantly moderates and mitigates the destructive effects of such anticipatory anxiety. Furthermore, this study uncovers sharp disparities in academic resilience driven by socio-economic stratification and geographical location. The synthesis of these findings necessitates a paradigmatic pedagogical reorientation shifting from pure knowledge transfer toward the cultivation of mental resilience thereby urging educational institutions to integrate proactive counseling and adaptive curricula to fortify student motivation against global disruptions.